2020
DOI: 10.3389/fmicb.2020.581283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Novel and Established Nitrification Inhibitors Relevant to Agriculture on Soil Ammonia- and Nitrite-Oxidizing Isolates

Abstract: Nitrification inhibitors (NIs) applied to soil reduce nitrogen fertilizer losses from agr o -ecosystems. NIs that are currently registered for use in agriculture appear to selectively inhibit ammonia-oxidizing bacteria (AOB), while their impact on other nitrifiers is limited or unknown. Ethoxyquin (EQ), a fruit preservative shown to inhibit ammonia-oxidizers (AO) in soil, is rapidly transformed to 2,6-dihydro-2,2,4-trimethyl-6-quinone imine (QI), and 2,4-dimethyl-6-ethoxy-quinoline (EQNL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 85 publications
(131 reference statements)
3
31
1
Order By: Relevance
“…Earlier studies by Papadopoulou et al ( 26 ) showed a clear and persistent inhibition of the transcription of amoA genes of both AOA and AOB by QI applied at rate of 16.1 mg kg −1 d.w. soil (i.e., approximately half of the high QI dose in the current study) in an alkaline soil (pH 7.9). The weaker effect of QI on AOB in the current study is probably a function of the lower dose rate of QI used in this study (10 mg kg −1 d.w. soil) compared to our earlier study and reflects the lower intrinsic sensitivity of AOB to QI compared to AOA ( 27 ).…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Earlier studies by Papadopoulou et al ( 26 ) showed a clear and persistent inhibition of the transcription of amoA genes of both AOA and AOB by QI applied at rate of 16.1 mg kg −1 d.w. soil (i.e., approximately half of the high QI dose in the current study) in an alkaline soil (pH 7.9). The weaker effect of QI on AOB in the current study is probably a function of the lower dose rate of QI used in this study (10 mg kg −1 d.w. soil) compared to our earlier study and reflects the lower intrinsic sensitivity of AOB to QI compared to AOA ( 27 ).…”
Section: Discussioncontrasting
confidence: 48%
“…Our hypothesis fits well with the theory that nonrandom associations exist between different AOM and NOB lineages that, along with edaphic factors, shape field-scale spatial patterns of nitrifying communities ( 52 ). Still a higher intrinsic tolerance of Nitrospira over Nitrobacter to NIs cannot be excluded, although data from relevant in vitro assays are only available for Nitrobacter ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. Nitrosotalea (S) is an ammonia oxidizer found in acidic agricultural soil [107][108][109][110], which is the case in our study as the CCC rotation has the lowest pH. Lehtovirta-Morley, et al [111] and Papadopoulou, Bachtsevani, Lampronikou, Adamou, Katsaouni, Vasileiadis, Thion, Menkissoglu-Spiroudi, Nicol, and Karpouzas [110] both confirmed that C. Nitrocosmicus (S) occupy contrasting ecological niches compared to C. Nitrosotalea (S) and C. Nitrocosmicus is present in larger RAs at neutral pH. The unspecified AOA Nitrososphaeraceae (F) showing elevated RAs from the SSS rotation matches Behnke, Zabaloy, Riggins, Rodriguez-Zas, Huang, and Villamil [25].…”
Section: Discussionmentioning
confidence: 99%